Perancangan Ulang Produk Kruk Dengan Metode Quality Function Deployment Untuk Memenuhi Kebutuhan Penyandang Disabilitas Kaki - Apriani, Ratna; Emirbuwono Basuki, Demas (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
The population of persons with disabilities in Indonesia is currently estimated at approximately 22.97 million individuals, representing around 8.5% of the national population. Among this group, persons with lower-limb disabilities constitute the largest proportion, accounting for roughly 38% of all individuals with disabilities. This category of disability is frequently associated with significant challenges in mobility, including difficulties in walking, ascending stairs, and performing other related movements. Consequently, lower-limb disability users commonly depend on assistive devices such as crutches to support their daily activities. However, complaints often arise when using crutches, one of which is the difficulty of using crutches when traveling, whether by motorcycle or car, due to the elongated size of the device. To address these issues, a Quality Function Deployment (QFD) approach was employed to redesign the crutch in accordance with user needs. Based on this study, improvements were made in two aspects: economic and ergonomic. The product was adjusted to ensure that the price is acceptable to users. In addition, a redesign of the crutch dimensions was carried out, resulting in an increase in height. This modification aims to enhance ergonomic comfort and prevent potential secondary health problems for the users